2012
DOI: 10.1111/jeb.12008
|View full text |Cite
|
Sign up to set email alerts
|

From nature to the laboratory: the impact of founder effects on adaptation

Abstract: Most founding events entail a reduction in population size, which in turn leads to genetic drift effects that can deplete alleles. Besides reducing neutral genetic variability, founder effects can in principle shift additive genetic variance for phenotypes that underlie fitness. This could then lead to different rates of adaptation among populations that have undergone a population size bottleneck as well as an environmental change, even when these populations have a common evolutionary history. Thus, theory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 85 publications
3
55
1
Order By: Relevance
“…A signiÞcant limitation of laboratory rearing of small populations is genetic bottlenecking through founder effect and genetic drift which can result in signiÞcant reduction in genetic variation (Santos et al 2012). Based on results from our bioassays, the laboratoryreared reference strain (GR) appears to be distinct from the reference strain previously described as having full susceptibility to broad-spectrum insecticides (Forrester et al 1993, Gunning et al 1996a.…”
Section: Discussionmentioning
confidence: 99%
“…A signiÞcant limitation of laboratory rearing of small populations is genetic bottlenecking through founder effect and genetic drift which can result in signiÞcant reduction in genetic variation (Santos et al 2012). Based on results from our bioassays, the laboratoryreared reference strain (GR) appears to be distinct from the reference strain previously described as having full susceptibility to broad-spectrum insecticides (Forrester et al 1993, Gunning et al 1996a.…”
Section: Discussionmentioning
confidence: 99%
“…Insects have been mass reared over many generations for a variety of reasons, including biological control (Mackauer 1976, Nunney 2003, van Lenteren 2003, sterile insect release (Gilchrist et al 2012, Sorensen et al 2012, Weldon et al 2013, and basic studies of genetics and evolution (Hoffmann et al 2001, Santos et al 2012. Insect populations subjected to many generations of artiÞcial selection in the laboratory may change genetically in ways that improve their performance in the rearing facility but reduce their performance in the Þeld (Mackauer 1976, Nunney 2003, van Lenteren 2003, Chambers 1977, Sorensen et al 2012.…”
mentioning
confidence: 99%
“…We found that all populations adapt during the first generations, though at different rates (Simões et al, 2008a). We have also studied the evolutionary dynamics of several neutral molecular markers in these foundations (Simões et al, 2008b, 2010; Santos et al, 2012, 2013). The joint analyses of molecular markers and life-history traits showed that most differences in adaptive rates were due to sampling effects during the early stages of colonization (Santos et al, 2012).…”
mentioning
confidence: 99%
“…We have also studied the evolutionary dynamics of several neutral molecular markers in these foundations (Simões et al, 2008b, 2010; Santos et al, 2012, 2013). The joint analyses of molecular markers and life-history traits showed that most differences in adaptive rates were due to sampling effects during the early stages of colonization (Santos et al, 2012). These results illustrate that evolution in a novel environment may be strongly contingent: not only on the initial composition of a newly founded population, but also on the stochastic changes that occur during the first generations of colonization.…”
mentioning
confidence: 99%
See 1 more Smart Citation